Application of Ultraviolet LED for Sterilizing in Water Purifier - Tran, Thien Duc; Le, Minh Tan; Tran, Thu Thuy; Vu, Duy Dat; Cao, Xuan Truong; Nguyen, Dinh Huu Duc (Old Journal, 2018)
UVC LED with a wavelength of 275 nm and emission power of 4.5 mW was applied to sterilize in water purifier. The ability to sterilization of water purifier was studied on E.coli bacteria. E.coli bacteria were added into the water sample with a concentration of 6800 CFU/100 mL before irradiating. The irradiating time is set up at different values of 15 s; 30 s; 60 s. The result shows that, the bacteria concentration rapidly decreases with an increase of irradiating time. With the duration of 30 s, the bacteria concentration after irradiating is about 3 CFU/100 ml, corresponding to the sterilization ratio of 99,995%. The UVC LED system was also designed to optimize the irradiating area and time, thereby the sterilization efficiency will be enhanced.